ANALISIS SWOT SEBAGAI DASAR STRATEGI BRANDING PADA MADRASAH IBTIDAIYAH ALHIDAYAH, CIREUNDE, CIPUTAT - Iis Mei Susilawati; Muhammad Harun (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
This study aims to determine the strengths and weaknesses of MI Al-Hidayah, opportunities and threats that will be faced MI al-Hidayah, and what the appropriate branding strategy for MI al-Hidayah. This research uses qualitative approach. Data collection techniques are done by observation and interview. Key informants in this study were principals and some teachers who were directly involved in the school management process. The results showed that MI Al-Hidayah has a good enough strength and this can be utilized to win the competition in the field of education. Opportunities owned MI Al-Hidayah has been utilized optimally by MI Al-Hidayah. The branding strategy owned by MI Al-Hidayah is with the tahfidz qur`an from class 1 s / d VI that not all MI have such a program. If tahfidz program continues to be maintained and developed then MI al-Hidayah will have its own brand known by the community. This research also suggests MI al-Hidayah to maintain good image in the eyes of the community. In addition, MI al-Hidayah is also advised to increase the intensity and quality of the delivery of information in a focused manner, especially promoting the existing programs in the school. Keywords: SWOT, strategy, branding